Composite material for transport layer in perovskite solar cell
By blending metal halides with fullerene materials to form a composite transport layer, the problem of insufficient mechanical strength of the electron transport layer in perovskite solar cells is solved, and better mechanical characteristics and battery efficiency are achieved.
Patent Information
- Application Number
- CN202380057158.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-21
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-14
AI Technical Summary
The electronic transport layer materials of existing perovskite solar cells, especially fullerene materials, are insufficient mechanical strength, resulting in possible layering problems during packaging and bending, affecting the nucleation and battery efficiency of subsequent layers.
Metal halides such as LiF, CsF or MgF2 are blended with fullerene material to form a composite transport layer, which increases the mechanical strength of the transport layer through blending and maintains the necessary electrical characteristics.
Improved mechanical properties of the transport layer, such as bending resistance, reduces the risk of stratification, and improves the overall efficiency and stability of the solar cell.
Smart Images

Figure CN119631601A_ABST
Abstract
Description
Background Art Technical Field
[0001] Embodiments described herein relate to solar cells, and more particularly to transport layers thereof. Background of the Invention
[0003] Photovoltaic cells (also known as solar cells) are devices that convert radiant light energy into electrical energy. While single-crystal solar cells dominate the current solar cell industry and offer the highest efficiency and lifetime, thin-film solar cells are gaining increasing attention due to their potential to implement economical in-line deposition and patterning processes. In addition, some thin-film solar cells can be flexible and can be applied to curved surfaces, mobile devices, or other components. One such emerging thin-film technology is perovskite solar cells. Existing electron transport layers used in perovskite solar cells are typically composed of a single bulk material, typically TiO2, SnO x Or organic materials such as C60 fullerene. In particular, fullerene materials are commonly used as transport layer materials when making perovskite solar cells for integration into tandem architectures. Summary of the invention
[0004] Solar cell stacks, in particular perovskite solar cell stacks, are described in which transport layers, in particular fullerene-based transport layers, are blended with metal halides such as LiF, CsF or MgF2. It has been observed that such a composition provides a basis for the subsequent growth of a durable buffer layer and provides improved mechanical properties such as bending resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0005] Figure 1A is an illustration of a solar cell stack according to one embodiment.
[0006] Figure 1B is an illustration of a tandem solar cell stack according to one embodiment.
[0007] Figure 1C is an illustration of a silicon-perovskite tandem solar cell stack according to one embodiment.
[0008] Figure 2 A schematic cross-sectional side view illustration of a control sample of a solar cell used for testing according to an embodiment is provided.
[0009] Figure 3 A schematic cross-sectional side view illustration of a solar cell having a blended electron transport layer for testing according to an embodiment is provided.
[0010] Figure 4is a graph showing the removal percentage of the perovskite absorber layer after the solvent buffer layer test for solar cells with different electron transport layer compositions according to the embodiments.
[0011] Figure 5 is a graph showing bending radii of solar cells having different electron transport layer compositions when layered according to the embodiment.
[0012] Figure 6 is a graph showing current-voltage electrical testing of solar cells with different electron transport layer compositions according to an embodiment.
[0013] Figure 7 is a graph showing normalized efficiency over time of solar cells with different electron transport layer compositions according to an embodiment. DETAILED DESCRIPTION
[0014] Embodiments describe solar cell stacks, and in particular perovskite solar cell stacks including blended transport layers.
[0015] In one aspect, it has been observed that common fullerene materials used in tandem solar cell architectures or other solar cells for flexible solar cell applications are mechanically weak and do not form a good surface for nucleating subsequent layers when processed by chemical vapor deposition (CVD), including atomic layer deposition (ALD). The mechanical weakness of the fullerene layer may cause delamination during encapsulation. The nucleation properties, in turn, affect the quality of subsequent layers. For example, in an exemplary hole transport layer (HTL)-perovskite-ETL architecture, an additional CVD metal oxide layer can be deposited above the fullerene ETL as a buffer layer to protect the underlying layers from sputtering deposition during the deposition of the subsequent front transparent electrode layer and / or as a diffusion barrier layer for the metal electrode layer. It has also been observed that the fullerene material increases the parasitic absorption of the ETL, reducing the efficiency of the tandem solar cell where light enters through the front side.
[0016] According to an embodiment, a perovskite solar cell stack is described in which a transport layer (e.g., ETL, HTL) comprises a metal halide (e.g., lithium fluoride (LiF), cesium fluoride (CsF), magnesium fluoride (MgF2)) blended with a fullerene material. For example, the metal halide can be evaporated simultaneously with the fullerene at a material loading of 20% or more (by volume). Metal halides such as LiF are hygroscopic and polar, and can adhere well to adjacent layers and facilitate nucleation of subsequent CVD processes for buffer layer deposition. The resulting composite transport layer can exhibit improved mechanical strength while maintaining the necessary electrical properties.
[0017] In various embodiments, description is made with reference to the accompanying drawings. However, certain embodiments may be practiced without one or more of these specific details, or in combination with other known methods and configurations. In the following description, many specific details, such as specific configurations, dimensions, and processes, etc., are described to provide a thorough understanding of the embodiments. In other cases, well-known semiconductor processes and manufacturing techniques are not particularly described in detail so as not to unnecessarily confuse the embodiments. Throughout this specification, reference to "one embodiment" means that the specific features, structures, configurations, or characteristics described in conjunction with the embodiment are included in at least one embodiment. Therefore, the phrase "in one embodiment" that appears everywhere throughout this specification does not necessarily refer to the same embodiment. In addition, specific features, structures, configurations, or characteristics can be combined in any suitable manner in one or more embodiments.
[0018] As used herein, the terms "above", "to", "between" and "on" may refer to the relative position of one layer with respect to other layers. A layer that is "above" or "on" another layer or is bonded to or "in contact with" another layer may be directly in contact with the other layer or may have one or more intervening layers. A layer that is "between" layers may be directly in contact with the layers or may have one or more intervening layers.
[0019] See now Figure 1A to Figure 1B , Figure 1A is an illustration of a solar cell stack according to one embodiment, and Figure 1B is an illustration of a tandem solar cell stack according to one embodiment. In the following description, various layers and components for a solar cell stack are described. It should be understood that each layer may include a single layer or multiple layers. In addition, references to bottom or top layers herein are relative and may not reflect the actual orientation in the product.
[0020] exist Figure 1A to Figure 1B In the particular embodiment shown, the solar cell 100 can absorb light from the bottom side of the illustrated stack, for example, through a transparent substrate 110. The transparent substrate 110 can be rigid or flexible. For example, the transparent substrate 110 can include a permanent or temporary carrier, such as glass and a top (flexible) polymer adhesive layer.
[0021] As illustrated, the solar cell 100 may include a bottom electrode layer 120, a top electrode layer 170, and a subcell 220 formed on a substrate 110. In addition, a buffer layer 160 may be formed on the subcell 220 (e.g., by CVD or ALD). The buffer layer 160 may additionally serve as a charge transport layer. In the specific embodiment illustrated, the buffer layer 160 may serve as both a barrier layer and a charge transport layer. The subcell 220 includes an absorption layer 140 and one or more transport layers. In the illustrated embodiment, the subcell 220 includes a hole transport layer (HTL) 130 above the bottom electrode layer 120, an absorption layer 140 above the HTL 130, and an electron transport layer (ETL) 150 above the absorption layer 140. The buffer layer 160 may also serve as an ETL in this configuration, and physically separates the top electrode layer 170 from the subcell 220, and specifically physically separates the absorption layer 140.
[0022] In a specific embodiment, the bottom electrode layer 120 is formed of a transparent material. Exemplary transparent bottom electrode materials include poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), transparent conductive oxides (TCOs) such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium zinc oxide (IZO), aluminum-doped zinc oxide (AZO), cadmium stannate, etc. HTL 130 may include one or more layers formed of metal oxides such as nickel oxide (NiOx) or vanadium oxide (V2O5), organic polymers such as poly (triarylamine) (PTAA) or small molecules such as 2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene (spiro-MeOTAD). HTL 130 may be additionally doped to increase conductivity and may include a double layer of a metal oxide (e.g., NiOx) and an organic layer (such as PTAA) on top.
[0023] The absorption layer 140 according to the embodiment may be formed of a perovskite material. The perovskite material may be characterized by the formula ABX3, wherein A represents a large atomic or molecular cation (e.g., Cs, methylammonium, formamidine, etc.), B represents a positively charged cation (e.g., metal, lead, lead salt, Sn), and X represents a negatively charged anion (e.g., halide, I, Br, Cl). The perovskite material may also include A 1 m A n B n-1 X 3n-1 A mixture of 2D and 3D structures in the family, where A 1 represents a positively charged cation (eg, butylammonium, phenethylammonium, guanidine, etc.) Alternative materials such as organic materials may also be used as the absorber layer.
[0024] The ETL 150 according to the embodiment may be formed of fullerenes blended with metal halides (e.g., lithium fluoride (LiF), cesium fluoride (CsF), magnesium fluoride (MgF2)). For example, the metal halide may be evaporated simultaneously with the fullerene at a material loading of 20% or more (by volume percentage). Metal halides such as LiF are hygroscopic and polar, and may adhere well to adjacent layers, and facilitate nucleation of subsequent CVD processes for buffer layer deposition. The buffer layer 160 according to the embodiment may be formed of an n-type metal oxide (such as tin oxide or aluminum zinc oxide (AZO)) above the fullerene layer. In one embodiment, the top electrode layer 170 includes one or more metal layers such as Ag, Cr, Au, Cu, Al, etc.
[0025] Figure 1B 1 is an illustration of a tandem solar cell stack according to an embodiment. The tandem structure may include a plurality of absorber layers, which may be of the same or different materials. In the specific embodiment described, the tandem structure is a perovskite-perovskite tandem structure, but the embodiment is not limited thereto. The electrode layer 120, the HTL 130, the absorber layer 140, and the ETL 150 may be similar to the embodiment of FIG. Figure 1A Similarly, HTL 230 may be similar to HTL 130, absorber layer 240 may be similar to absorber layer 140, and ETL 250 may be similar to ETL 150. It is worth noting that although absorber layers 140, 240 may be formed of similar perovskite-based materials, they may be tuned for different band gaps. One or more of the absorber layers may also be formed of organic materials. Recombination layer 255 may be located between stacked subcells 220, between ETL 250 and HTL 130. Recombination layer 255 may be a transparent conductive layer such as TCO, or specifically ITO. It may be similar to Figure 1A A buffer layer 160 and a top electrode layer 170 are additionally formed similarly.
[0026] Figure 1C is an illustration of an alternative tandem solar cell stack according to an embodiment. In particular, Figure 1C A silicon-perovskite tandem solar cell stack according to an embodiment is shown. In addition, the silicon-perovskite tandem solar cell stack can absorb light from the top side instead of the bottom side. The tandem structure can include similar Figure 1AThe HTL 130, the absorber layer 140 and the ETL 150 described above. Such a top perovskite cell can be formed on a lower silicon subcell 220 including a p-doped silicon layer 330 and an n-doped silicon layer 350. A recombination layer 355 can be located between the subcells 220. The recombination layer 355 can be formed of a transparent material similar to the recombination layer 255. Since the silicon portion can be opaque, the top electrode layer 170 can be formed of a transparent conductive layer such as poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium zinc oxide (IZO), aluminum-doped zinc oxide (AZO), cadmium stannate, etc. Transparent conductive oxide (TCO) is formed. A top metal pattern 180 can then be formed over the transparent top electrode layer 170, for example, to facilitate charge transport. In one embodiment, the top metal pattern is formed of a suitable material such as Ag, Cr, Au, Cu, Al, etc. The top metal pattern 180 may be formed in the shape of a finger electrode to transfer charge without excessively blocking light transmission. A back contact 310 may also be formed under the p-doped silicon layer 330. The back contact 310 may be formed of a suitable material such as Ag, Cr, Au, Cu, Al, etc.
[0027] In About Figures 1A to 1C In each of the aforementioned embodiments described, a specific stack having a pin or pn orientation is described and illustrated, but depending on the embodiment, the order of the electron transport layer and the hole transport layer can also be reversed. These changes in the order of layer formation can additionally change the material selection of some layers without departing from the principles of the embodiment. Therefore, depending on the embodiment, the reference to ETL or HTL can be reversed.
[0028] To demonstrate the effectiveness of blending metal halides with fullerene transport layers, various test samples were prepared and tested for solvent removal, delamination bending radius, and current-voltage curve characteristics. In each test, at least a control sample including a LiF:fullerene bilayer was prepared and compared to various LiF:fullerene blends with different LiF loadings.
[0029] Control samples
[0030] See now Figure 2, a schematic cross-sectional side view illustration of a control sample for testing according to an embodiment is provided. As shown, the control sample is formed by forming a 25 μm thick polyethylene terephthalate (PET) adhesion layer 114 on a glass carrier substrate 112. A 75nm-200nm thick ITO bottom electrode layer 120 is then deposited. A double-layer HTL 130 is then formed, which includes a first 40nm thick metal oxide layer and a top 5nm-10nm thick organic layer, or more specifically PTAA. HTL 130 is followed by a 400nm-600nm thick perovskite absorber layer 140. ETL 150 can then be formed on the perovskite absorber layer 140.
[0031] exist Figure 2 In the particular control sample illustrated in FIG, an initial 0.5 nm-2 nm thick LiF wetting layer 152 is deposited, followed by a 10 nm-30 nm fullerene bulk ETL 150 and a 15 nm thick metal oxide (SnOx) buffer layer 160. A top electrode layer 170 is then formed over the buffer layer 160. A thin adhesion layer (e.g., 10 nm thick oligomers and polymers) such as perylene derivatives or polymers or ethoxylated polyethyleneimine may optionally be located between the bulk ETL 150 and the buffer layer 160.
[0032] LiF:Fullerene blend samples
[0033] See now Figure 3 , prepared similar to Figure 2 150 . As shown, the ETL 150 still includes a 0.5nm-2nm thick LiF wetting layer 152, followed by a 10nm-30nm thick LiF:fullerene blend bulk ETL 150. According to an embodiment, various different LiF loadings are blended with fullerenes and vapor deposited simultaneously. Depending on the test sample, the blend amount varies between 1%, 5%, 25%, 33%, 67% and 75%. After depositing the bulk ETL 150, a 15nm thick SnOx buffer layer 160 and a top electrode layer 170 are deposited. A thin adhesion layer (e.g., 10nm thick oligomers and polymers) such as perylene derivatives or polymers or ethoxylated polyethyleneimine may optionally be located between the bulk ETL 150 and the buffer layer 160.
[0034] Solvent buffer test
[0035] To test the barrier quality of the buffer layer 160, control samples and LiF:fullerene blend samples of 33% LiF and 67% LiF (by volume) were exposed to dimethylformamide (DMF) solvent for the same period of time and then measured for the remaining weight % of the underlying perovskite absorber layer. Figure 4 The results presented show that about 90% of the initial perovskite absorber layer was dissolved in the control sample, while about 15% of the perovskite absorber layer was dissolved in the 33% LiF:fullerene blend, and about 10% of the perovskite absorber layer was dissolved in the 67% LiF:fullerene blend. These results indicate that the quality of the buffer layer 160 grown on top of the HTL bulk layer comprising the LiF:fullerene blend exhibits significantly improved barrier properties.
[0036] Bending radius test
[0037] It has been observed that the fullerene layer in particular has both weak cohesion to itself and weak adhesion to adjacent layers. This can be a prohibitive property for flexible perovskite solar cells and can lead to delamination in flexible encapsulated solar cells and modules. To test the mechanical strength of the LiF blended fullerene layer, a bend radius test was performed to measure the bending radius until delamination occurs within the fullerene layer or from adjacent layers. The results are provided in Figure 5 As shown in the figure, for the control sample, delamination was detected at a bending radius of about 0.75 cm. Even with the addition of a small amount of LiF, the bending radius test was significantly improved, with the bending radius results of 0.35 cm for the 5% and 10% LiF blends, 0.225 cm for the 33% LiF blend, and further improved at 0.065 cm for the 67% LiF blend. Therefore, the bending radius test shows an improvement with increasing LiF loading. The improvement expected to be increased is due to an increase in both cohesion and adhesion strength.
[0038] Electrical Testing
[0039] To verify that the LiF-blended fullerene layer maintains adequate electrical properties relative to the control sample composition, various samples were prepared and tested by current-voltage (iV) curves showing both open circuit voltage (Voc) (where the curve crosses the 0 current value) and series resistance (which corresponds to the slope of the curve at a far forward bias, i.e., a forward bias greater than the open circuit voltage). More specifically, a steeper slope corresponds to a lower series resistance and a higher fill factor of the solar cell.
[0040] See now Figure 6The results provided in show a first control sample (Control 1) in which the LiF wetting layer 152 is omitted. A second control sample (Control 2) is also demonstrated in which a 1 nm thick LiF wetting layer 152 is provided. Each of these samples represents a lower limit and an upper limit of the open circuit current voltage (Voc), respectively. As shown, including a LiF wetting layer 152 below the fullerene (C60) bulk ETL 150 improves Voc, but increases the series resistance. The third control sample (Control 3) with three wetting layers exhibits intermediate Voc results and lower series resistance. The blending of LiF with fullerene in the bulk ETL 150 shows some Voc performance gains compared to Control 1 and an improved slope compared to Control 2, which corresponds to a reduced series resistance. The battery with LiF blended into the ETL exhibits a lower series resistance than control samples 1 to 2, with the 25% LiF blend exhibiting a lower series resistance than the 75% LiF blend. This indicates that the blending approach achieves the improved open circuit voltage associated with the insertion of the LiF wetting layer while also reducing the series resistance of the cell, which can be attributed to the enhanced conductivity of the fullerenes. Furthermore, the improved series resistance suggests that multiple wetting layers, such as Control 3, can be omitted.
[0041] Although the above-mentioned test samples have been specifically related to the blending of LiF and fullerene, the embodiment is not limited to LiF and may include other metal halides. For example, when CsF or MgF2 is used to replace LiF, similar effects can be observed. Specifically, LiF: fullerene blend samples are prepared as described above, and the series resistance and open circuit voltage are tested by irradiating the solar cell with a lamp of a standard solar spectrum (AM1.5G) and measuring the current-voltage (JV) curve. Specific samples and test results are provided in Table I, and each prepared sample has no buffer layer and has a metal top electrode layer. Similar samples were also prepared and tested by replacing LiF with CsF. Specific samples and test results are provided in Table II, and each sample includes a buffer layer and a metal top electrode layer. In addition, other samples of LiF with slightly different perovskite components and MgF2 replacement were prepared and tested. Specific samples and test results are provided in Table III below, and each sample includes a buffer layer and a metal top electrode layer.
[0042] Table I.
[0043] <![CDATA[Series resistance (ohm cm 2 )]]> Open circuit voltage(V) Control 1 (C60 only, no LiF) 3.75 1.08 Control 2 (1nm LiF / C60 double layer) 4.76 1.15 25%LiF:C60 blend 3.00 1.12 75%LiF:C60 blend 3.00 1.15
[0044] Table II.
[0045] Open circuit voltage(V) efficiency(%) Control 2 (1nm LiF / C60 double layer) 1.12 17 33% CsF:C60 blend 1.1 14.2 67% CsF:C60 blend 1.125 14.2 1nm LiF / 67%CsF:C60 blend double layer 1.125 15
[0046] Table III.
[0047]
[0048] As shown in Tables I and II, in an architecture without a LiF wetting layer, blending CsF into fullerenes also improves the open circuit voltage, similar to the performance observed when LiF is blended into the ETL layer. Similar high concentrations of CsF can be used to achieve effective devices, which unexpectedly shows that device performance can be maintained at such high insulator loadings such as CsF and LiF. Another experiment using cesium carbonate (CsCO3) was also conducted, and no functional device was produced. This shows that alkali halides have unique properties that allow them to be included in the ETL layer at very high concentrations, which improves or does not significantly degrade device performance while also enhancing mechanical properties and suitability for CVD (including ALD) layer growth. The results of Table III further support that functional devices can also be achieved with the alkaline earth halide MgF2.
[0049] Accelerated Aging Test
[0050] In addition to physical and electrical requirements, the feasibility of blending ETL components may also require maintaining a certain efficiency over a specified lifetime. To quantify this accelerated aging test, a solar cell stack including a control sample (LiF / C60 bilayer) and LiF:fullerene blends with 25% and 67% fullerene was subjected to accelerated aging tests, with each test sample maintained at approximately 40°C and irradiated with the equivalent of 1 sun (AM1.5 spectrum) while being maintained at its maximum power point over time. Figure 7 Each sample in the includes a buffer layer and a metal top electrode layer. The test results are provided in Figure 7 , where it is shown that the 25% LiF blend maintains the best normalized efficiency over time, while the 67% LiF blend exhibits a significant decrease in efficiency. These results indicate that the blended transport layer according to the embodiments may contain less than 67% metal halide by volume. More specifically, the blended transport layer may contain 60% or less, or more specifically 50% or less, or even 40% or less metal halide by volume. Referring again to the bend test results, the blended transport layer may contain at least 10%, or more specifically at least 20% metal halide by volume. In an exemplary embodiment, the blended transport layer contains 20% to 60% metal halide, or more specifically 20% to 50% metal halide, or even more specifically 20% to 40% metal halide, such as 33% metal halide by volume.
[0051] Thermal stress test
[0052] The ability to withstand thermal stress may be an additional factor when selecting viable solar cell components. A solar cell stack including a control sample (LiF / C60 bilayer) ETL and an ETL of a LiF:fullerene blend containing 25% and 75% LiF by volume was thermally stressed. Each of the three samples did not include a buffer layer and a metal top electrode layer. All three samples were kept at approximately 85°C for 30 hours, and then tested for efficiency to determine the fraction of initial performance remaining after thermal stress. The results of the thermal stress testing are provided in Table IV below.
[0053] In the fourth sample, a buffer layer (such as tin oxide), a double-layer top electrode stack (such as an ITO-metal layer stack), and a double-layer ETL (the first 25 nm of the ETL is 50% LiF:fullerene composition, and the last 5 nm is 75% LiF:fullerene composition) are placed under a 85°C thermal stress test for 1,000 hours. These results are also presented in Table IV below. As shown in Table IV, the fourth sample does not lose any performance, indicating that good thermal stress performance can be achieved with a 50% LiF layer to form the bulk of the ETL.
[0054] Table IV.
[0055]
[0056] As shown in Table IV, solar cells with excessively high total metal halide content directly above the perovskite absorber layer have much lower stability when exposed to high temperatures (85°C), which may be relevant for operation on hot days and passing standard qualification tests, such as the damp heat test specified in the IEC (International Electrotechnical Commission) 61215 standard. For example, it is believed that a 10nm-30nm thick ETL layer with a 25% LiF:C60 blend passes the thermal stress test, while a 10nm-30nm thick ETL layer with a 75% LiF:C60 blend may have less suitable performance in the thermal stress test. In addition, a 10nm-30nm thick ETL bilayer with a 50% / 75% LiF:C60 blend (where 50% is closest to the perovskite absorber layer) also has suitable performance in the thermal stress test.
[0057] In one embodiment, the solar cell comprises a first electrode layer, an absorber layer, and a transport layer between the first electrode layer and the absorber layer. The transport layer may be a HTL or an ETL and comprises a metal halide and a fullerene blend. In one embodiment, the metal halide is blended throughout the entire thickness of the transport layer and may be blended uniformly throughout the entire thickness. In one embodiment, the transport layer is at least 5 nm thick, or more specifically at least 10 nm thick. In one embodiment, the metal halide is at least 20% by volume of the second transport layer, such as 20% to 75%, 20% to 60%, 20% to 50%, or 20% to 40%.
[0058] See also Figures 1A to 3 In the exemplary embodiment illustrated in FIG. 1 , in one embodiment, the transport layer is a first electron transport layer (ETL) 150. According to the embodiment, the metal halide may include materials such as LiF, CsF, MgF2, etc. For example, the metal halide may be fluorine (F)-containing or lithium (Li)-containing. Metal halide blending may also be used in the HTL 130. In one embodiment, the first HTL 130 includes a metal oxide layer. In one embodiment, the HTL 130 further includes an organic layer above the metal oxide layer.
[0059] One or more wetting layers 152 may optionally be located between the absorber layer 140 and the transport layer (e.g., ETL 150). In one embodiment, the wetting layer 152 includes a LiF layer. For example, the one or more wetting layers 152 may include a metal halide (e.g., LiF) layer, a fullerene layer, and multiple layers of various metal halide layers and fullerene layers. For example, the wetting layer may include a C60 / LiF / C60 triple layer, a LiF / C60 double layer, and the like.
[0060] According to an embodiment, the buffer layer 160 may be located between the transport layer (e.g., ETL 150) and the first electrode layer 170. In one embodiment, the buffer layer 160 includes a metal oxide such as SnOx, which may be optionally doped with aluminum. An adhesion layer may be optionally located between the buffer layer 160 and the transport layer (e.g., ETL 150).
[0061] The solar cell according to the embodiment can be a single cell, or a stack of multiple cells including series cells. In an exemplary pin arrangement, the solar cell includes a transparent electrode layer 120 below the absorber layer 140. In such a stack, the first (top) electrode layer 170 can include one or more metal layers. It should be understood that the embodiment is not limited to the pin arrangement, and can include a nip arrangement.
[0062] A tandem structure is also described. In one embodiment, the solar cell includes a tandem (e.g., perovskite) subcell. For example, the first ETL 150 and the first HTL 130 can be a portion of a first subcell 220 stacked on top of a second subcell 220, the second subcell including a second HTL 230, a second ETL 250 above the second HTL, and a second perovskite absorber layer 240 between the second HTL 230 and the second ETL 250. In one embodiment, the solar cell includes a tandem silicon-perovskite subcell. For example, the first ETL 150 and the first HTL 130 can be a portion of a first subcell 220 stacked on top of a second subcell 220 including a p-doped silicon layer and an n-doped silicon layer.
[0063] In utilizing various aspects of the embodiments, it will be apparent to those skilled in the art that combinations or variations of the above embodiments are possible to form a perovskite solar cell stack including a blended transport layer. Although the embodiments have been described in language specific to structural features and / or methodological acts, it should be understood that the appended claims are not necessarily limited to the specific features or acts described. The specific features and acts disclosed should be understood as embodiments that can be used to illustrate the claims.
Claims
1. A solar cell, comprising: bottom electrode; a bottom transport layer above the bottom electrode; an absorbent layer above the bottom transmission layer; a top transport layer over the absorber layer, wherein the top transport layer comprises a metal halide and a fullerene blend; and A top electrode layer is above the top transport layer.
2. The solar cell of claim 1, wherein the metal halide is blended throughout the entire thickness of the top transport layer.
3. The solar cell of claim 2, wherein the top transport layer is at least 5 nm thick.
4. The solar cell of claim 2, wherein the metal halide is uniformly blended throughout the entire thickness of the top transport layer.
5. The solar cell of claim 2, wherein the metal halide comprises at least 20% by volume of the top transport layer.
6. The solar cell of claim 2, wherein the metal halide comprises 20% to 75% by volume of the top transport layer.
7. The solar cell of claim 2, wherein the metal halide constitutes 20% to 60% by volume of the top transport layer.
8. The solar cell of claim 2, wherein the metal halide comprises 20% to 50% by volume of the top transport layer.
9. The solar cell of claim 2, wherein the metal halide comprises 20% to 40% by volume of the top transport layer.
10. The solar cell of claim 2, further comprising a wetting layer between the absorber layer and the top transmission layer. The solar cell according to claim 10 , wherein the wetting layer comprises LiF or fullerene. 12 . The solar cell of claim 1 , further comprising a buffer layer between the top transport layer and the absorber layer, wherein the top transport layer is a first electron transport layer (ETL). The solar cell according to claim 12 , wherein the metal halide comprises Li. The solar cell according to claim 12 , wherein the metal halide comprises F. The solar cell according to claim 12 , wherein the buffer layer comprises a metal oxide.
16. The solar cell according to claim 15, wherein the metal oxide is doped with aluminum. 17 . The solar cell according to claim 15 , further comprising an adhesion layer between the buffer layer and the ETL.
18. The solar cell of claim 15, wherein the absorber layer is a perovskite absorber layer.
19. The solar cell of claim 18, wherein the bottom transport layer, the perovskite absorber layer, and the top transport layer are part of a first subcell of a tandem solar cell, wherein the tandem solar cell further comprises a second subcell below the first subcell, the second subcell comprising a second perovskite absorber layer.
20. The solar cell of claim 18, wherein the bottom transport layer, the perovskite absorber layer, and the top transport layer are part of a first subcell of a tandem solar cell, wherein the tandem solar cell further comprises a second subcell below the first subcell, the second subcell comprising a p-doped silicon layer and an n-doped silicon layer.
21. The solar cell according to claim 1, wherein: said metal halide being blended throughout the entire thickness of said top transmission layer; The metal halide constitutes 20% to 60% by volume of the top transport layer; and The absorption layer is a perovskite absorption layer.
22. The solar cell of claim 21 wherein the metal halide comprises 20% to 60% by volume of the top transport layer.
23. The solar cell of claim 21, wherein the metal halide comprises F.
24. The solar cell of claim 21 further comprising a buffer layer between the top transmission layer and the top electrode layer.
25. The solar cell of claim 24, wherein the buffer layer comprises a metal oxide.